Criminal Sanction Approach to Liwath (Gay) and Musahaqah (Lesbian) Behavior in Qanun Jinayah Number 6 of 2014 - Deswita Keumala Ulfah; Mohd. Din; Ali Abubakar (Syiah Kuala Law Journal, 2021)
Gay and lesbian behavior has entered and developed in Aceh in the aftermath of the 2004 tsunami. As an area that is implementing Islamic law, the issue has become the focus of the community, religious scholarships, and the Aceh Government. Since Qanun Jinayah No. 6 of 2014 applies, there are only 3 (three) liwath cases which were tried with caning by the Syar'iyah Court of Banda Aceh City. The results of law enforcement research on liwath (gay) and Musahaqah (lesbi) perpetrators have not been able to provide a deterrent effect, because the more widespread this behavior develops in society. Additional sanctions should be proposed in the form of actions, such as counseling assistance, religious assistance, and social and health assistance. It is hoped that sanctions will change the behavior of gays and lesbians in terms of their sexual orientation.